Hubungan Antara Karakteristik dengan Kadar Ferritin pada Ibu Hamil Trimester III di Puskesmas Jagir Surabaya - Nur Masruroh; Gilang Nugraha (Jurnal Sehat Mandiri, 2020)
Ferritin is an iron storage protein and is extracellular in serum. Ferritin serum functions as a clinical marker of the body's iron stores status. Low ferritin levels illustrate the low iron stores that lead to iron deficiency conditions resulting in anemia in pregnant women. Some maternal characteristics affect ferritin levels in pregnant women.This study aims to determine the relationship between characteristics with ferritin levels. Taking the location of the research at the Jagir Public Health Center in Surabaya with a sample of 30 respondents who met the inclusion and exclusion criteria. The research method was observational analytic by taking maternal venous blood to be examined for ferritin levels then looking for the relationship with the characteristics of pregnant women and analyzed using chi square. More than half (83%) of respondents had ferritin levels <30 µg / ml. The results of the analysis using chi square (p = <0.05) show that there is a relationship between age (0.04) and parity (0.01) with ferritin levels. No relationship between education (0.71) and employment (0.23) with ferritin levels. Age and parity were related to ferritin levels. Education and work are not related to ferritin levels for pregnant women in the third trimester. It is expected that pregnant women increase consumption of foods that contain lots of iron to prevent anemia and health workers provide socialization of foods that contain lots of iron.